2018
DOI: 10.1177/2280800018782840
|View full text |Cite
|
Sign up to set email alerts
|

Nanotribological response of a-C:H coated metallic biomaterials: the cases of stainless steel, titanium, and niobium

Abstract: Background Wear and corrosion have been identified as two of the major forms of medical implant failures. This study aims to improve the surface, protective and tribological characteristics of bare metals used for medical implants, so as to improve scratch resistance and increase lifetime. Methods Hydrogenated amorphous carbon (a-C:H) films were deposited, using plasma enhanced chemical vapor deposition (PECVD), on stainless steel (SS), titanium (Ti) and niobium (Nb) metal plates. Nanomechanical and nanotribol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Further studies are required to validate these findings [72]. In a study, hydrogenated amorphous carbon (a-C:H) films were deposited using plasma-enhanced CVD on MSS, Ti, and Nb, and were found to reduce the roughness and coefficient of friction while improving the tribomechanical response [28]. The influence of In a study, hardystonite bioceramic (Ca 2 ZnSi 2 O 7 ) was coated onto MSS using ED and showed improved corrosion resistance and bioactivity [39].…”
Section: Improvement Of Physical Inflammatory and Miscellaneous Prope...mentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies are required to validate these findings [72]. In a study, hydrogenated amorphous carbon (a-C:H) films were deposited using plasma-enhanced CVD on MSS, Ti, and Nb, and were found to reduce the roughness and coefficient of friction while improving the tribomechanical response [28]. The influence of In a study, hardystonite bioceramic (Ca 2 ZnSi 2 O 7 ) was coated onto MSS using ED and showed improved corrosion resistance and bioactivity [39].…”
Section: Improvement Of Physical Inflammatory and Miscellaneous Prope...mentioning
confidence: 99%
“…In a study, hydrogenated amorphous carbon (a-C:H) films were deposited using plasmaenhanced CVD on MSS, Ti, and Nb, and were found to reduce the roughness and coefficient of friction while improving the tribomechanical response [28]. The influence of HA on the key physical properties of MSS using electrochemical deposition was also reported [245].…”
Section: Improvement Of Physical Inflammatory and Miscellaneous Prope...mentioning
confidence: 99%
“…Stents are cylindrically shaped, hollow mesh metal structures used to restore the flow in blood vessels and ducts . The corrosion resistance of implant materials results from optimal surface treatments during the manufacturing process, such as electropolishing, acid passivation, and protective coatings. Although this passivating film insulates the bulk material from the corrosive physiologic fluids, any mechanically induced break or defect in it increases the risk of corrosion . While metal alloys might endure significant forward and reverse mechanical strain excursions, the presence of a nonsuperelastic oxide layer could lead to cracking.…”
Section: Introductionmentioning
confidence: 99%
“…Pure titanium is one of the biomaterials that has been used in implant manufacturing due to its inherent properties and exceptional corrosion resistance [28][29][30]. In recent times, niobium has also gained considerable attention due to its enhanced properties and potential use in biomedical applications [31][32][33]. The addition of these reinforcements has been selected so as to maintain the austenitic structure of the developed compositions.…”
Section: Introductionmentioning
confidence: 99%